Risk factors associated with carbapenemase-producing enterobacterales (CPE) positivity in the hospital wastewater environment - Park, SC; Parikh, H; Vegesana, K; Stoesser, N; Barry, KE; Kotay, SM; Dudley, S; Peto, TEA; Crook, DW; Walker, AS; Mathers, AJ (American Society for Microbiology, 2020)
Background:Hospital wastewater is an increasingly recognized reservoir for resistant Gramnegative organisms. Factors involved in establishment and persistence of Klebsiella pneumoniae carbapenemase-producing organisms (KPCO) in hospital wastewater plumbing are unclear. Methods: This study was conducted at a hospital with endemic KPCO linked to wastewater reservoirs and robust patient perirectal screening for silent KPCO carriage. Over five months, both rooms occupied and not occupied by KPCO-positive patients were sampled at three wastewater sites within each room (sink drain, sink P-trap, and toilet or hopper). Risk factors for KPCO positivity were assessed using logistic regression. Whole genome sequencing (WGS) identified environmental seeding by KPCO-positive patients.